Інституціоналізація блокчейн-технологій у бухгалтерському обліку та аудиті - Замлинський, Віктор; Наконечна, Оксана; Ступницька, Тетяна; Городніченко, Станіслав (Odesa National University of Technology, 2025)
The application of blockchain technologies in accounting and auditing is transforming traditional principles of recording, verification, and validation of financial information, providing a new level of transparency, reliability, and process automation. The aim of this article is to conduct a comprehensive study of institutional models for the implementation of blockchain technologies in Ukraine, assess the readiness of financial and accounting systems for DLT integration, and identify strategic directions for institutionalization to enhance transparency, cybersecurity, and compliance with international standards (IFRS, ISA, MiCA, DORA). The study is based on methods of systemic and comparative analysis, content analysis of scientific publications and regulatory documents, SWOT analysis of institutional and technological capacities, and a review of international experience in implementing DLT in accounting and auditing. The analysis covers key technology components – distributed ledgers, smart contracts, and cryptographic mechanisms – and their role in building digital trust, automating financial processes, and enabling continuous auditing. The results indicate that effective institutionalization of blockchain technologies requires harmonization of the regulatory environment, development of professional competencies, advancement of adaptive institutional design models, and enhancement of digital infrastructure. It has been established that Ukraine’s institutional and technological readiness is currently at the pilot project stage and necessitates a comprehensive approach to regulatory, personnel, and cybersecurity support. The proposed strategic directions aim to create conditions for safe and large-scale use of DLT, increase trust in financial reporting, and integrate the national accounting and auditing system with international standards. The implementation of blockchain technologies lays the groundwork for transparent resource management, automation of financial processes, and strengthening Ukraine’s competitiveness in the global digital economy.